The Effects of Topic Familiarity on Kurdish EFL University Students’ Meaning Construction - Zheen Hamad Amin Abdullah; Nada Jabbar Abbas (Zanco Journal of Humanity Sciences)
This study investigates the effects of topic familiarity on meaning construction skills among Kurdish EFL university students. Recognizing vocabulary as a critical component of language learning, the research addresses the challenges Kurdish students face in understanding and acquiring new vocabulary within unfamiliar contexts. The study aims to analyze how familiarity with a topic influences students' ability to construct meaning from English texts. Utilizing an experimental design, 50 sophomores from the College of Education participated in pre- and post-tests, supported by topic familiarity questionnaires and a Vocabulary Knowledge Scale. Results indicate that the experimental group, exposed to reading materials aligned with familiar topics, showed significantly greater improvements in comprehension skills compared to the control group. The findings suggest that integrating familiar content into language instruction enhances student engagement and comprehension. The study concludes with recommendations for educators to incorporate familiar subjects into reading materials, employ structured meaning construction models, and balance familiar and challenging content to develop comprehensive reading skills. This approach not only reinforces vocabulary retention but also facilitates deeper cognitive processing and overall language acquisition.